Metropolitan mosaics and melting-pots : Paris and Montreal in francophone literatures - Murdoch, H. Adlai; De Souza, Pascale (Cambridge Scholars Publishing, 2013)
"Migration is both a demographic and a cultural phenomenon. As such, it both reshapes the global village and subverts the all-encompassing vision of the city, a space split between the blending of all new cultures and the need felt by many migrants to maintain their traditions and thereby contribute to a multicultural mosaic. This series of essays explores how the concepts of the melting-pot and the mosaic have shaped the representation of Paris and Montreal in francophone literatures. Migrant movements to these cities from the Caribbean, the Maghreb, Sub-Saharan Africa, Quebec, Indochina, and the Indian Ocean have produced new groups of intersecting cultures. Under the dual influences of their native and host countries, migrants have produced an innovative and multifaceted literature that reflects their composite world-view. Their writing poses pressing questions of ethnicity, immigration, integration, and citizenship, and challenges longstanding notions both of the concept of the city and of how its spaces embody and articulate Frenchness in the face of ongoing change. Such shifts produce changes not only in the diasporic culture, but in the national culture as well, through creolization processes. These shifting identities increasingly destabilize current notions of national membership and social and cultural belonging, since we can no longer presume a direct correspondence between place, culture, language and identity. They also pose new questions of national identity and difference as the immigrant presence expands and inflects the cosmopolitan pluralism of today's societies"--Provided by publisher